RELEVANSI TEORI PENGEMBANGAN KURIKULUM TYLER, TABA, DAN EISNER DALAM PENGUATAN KURIKULUM PENDIDIKAN AGAMA ISLAM ABAD 21 - Ani Maghfiroh; Khoirul Khasanah; Lailatul Qodriyah (Inteligensi : Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the relevance of curriculum development theories proposed by Ralph Tyler, Hilda Taba, and Elliot Eisner in strengthening the Islamic Religious Education (PAI) curriculum to address 21st-century challenges. Amidst the demands of the digital era, PAI requires a robust conceptual foundation to balance competency achievement with character formation. This study employs a qualitative library research method utilizing a philosophical-pedagogical approach. Data were collected from the scholars' primary works and recent literature, then analyzed using content analysis techniques. The results indicate that the three theories offer complementary strategic contributions: (1) Tyler's theory provides a rational structure through clear competency-based objectives and measurable evaluation; (2) Taba's theory offers a grassroots approach that empowers teachers to diagnose student needs contextually; and (3) Eisner's theory reinforces the aesthetic dimension and hidden curriculum for the internalization of spiritual values. It is concluded that the revitalization of PAI requires a synthesis of these three paradigms. The integration of Tyler's accountability, Taba's flexibility, and Eisner's humanism produces an adaptive, innovative, and holistic PAI curriculum design aimed at shaping a generation with noble character in the era of globalization.